Comparative effects of mineral fertilizer and digestate on growth, antioxidant system, and physiology of lettuce under salt stress - Li, Faqinwei; Yuan, Yongheng; Gong, Pengxuan; Imazumi, Yoshiaki; Na, Risu; Shimizu, Naoto (Horticulture, Environment, and Biotechnology, 2023)
Salt stress in plants presents a major challenge to future agricultural production. Digestate has various effects on plant growth, but little information is available on its effects on the antioxidant system and physiological characteristics of lettuce under salt stress. In this study, the impacts of mineral fertilizer and digestate application on edible parts of lettuce were compared under three salinities. Experimental treatments comprised application of two types of fertilizer (mineral fertilizer and digestate) and three NaCl concentrations (0, 3, and 7.5 dS m − 1 ). High NaCl concentrations resulted in significantly lower photosynthesis, growth, and physiological indices compared with those under no NaCl addition. However, under the 7.5 dS m − 1 NaCl condition, digestate application (DA) increased the fresh weight (42%), dry weight (27%), photosynthetic pigment contents and photosynthesis (20%) of lettuce compared with that under mineral fertilizer application (MFA). Accumulation of reactive oxygen species was markedly lower, and the membrane stability index was therefore higher, under DA compared with under MFA within the same salinity level. Lipid peroxidation was lower under DA compared with under MFA in all salinity treatments. Salt stress up-regulated the antioxidant system and DA further increased the enzymatic and non-enzymatic antioxidant capability compared with that under MFA. In addition, the total water use was lower and water-related indices, such as water use efficiency of fresh weight, water use efficiency of dry weight and relative water content, were higher under DA compared with under MFA. The application of digestate instead of mineral fertilizer could be a promising practice to alleviate the negative impact of salt stress on the productivity and physiological characteristics of lettuce plants.